Reconstructing Principles of Islamic Education in Qur’anic Exegesis and Their Application in Modern Education - Mastoni Mastoni; Abdul Aziz (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study explores the fundamental principles of Islamic education as derived from Qur’anic exegesis and examines their application within contemporary educational contexts. Using a qualitative literature review approach, the research integrates classical Qur’anic interpretations with recent scholarship in Islamic and educational studies to construct a coherent conceptual framework. The analysis identifies four foundational principles tawḥīd (divine unity), universality, balance (wasathiyyah), and raḥmah (compassion)as central to the Islamic educational worldview. These principles operate simultaneously as epistemological foundations, ethical orientations, and pedagogical guidelines that connect spiritual consciousness, intellectual development, moral cultivation, and social responsibility. The findings demonstrate that when Qur’anic principles are thematically interpreted and systematically embedded within curriculum design and pedagogical practice, Islamic education offers a holistic and adaptive model capable of responding to contemporary educational challenges. This study contributes to the field by articulating an integrative framework that bridges classical Qur’anic foundations with modern educational demands, positioning Islamic education as a transformative and contextually relevant paradigm in plural and dynamic societies.